Rapid cyclic ion mobility separations of monosaccharide building blocks as a first step toward a high-throughput reaction screening platform for carbohydrate syntheses. Issue 63 (14th December 2021) - Peterson, Tyler L.; Nagy, Gabe
Abstract : High-resolution cyclic ion mobility separations enable the rapid resolution of α/β anomers in carbohydrate building blocks and their associated anomeric impurities. Abstract : Herein we present a new high-throughput screening method for carbohydrate syntheses based on cyclic ion mobility spectrometry-mass spectrometry (cIMS-MS)-based separations. We rapidly resolved the α/β anomers for carbohydrates with varying protecting groups after only 5 m of cIMS-MS separation and also detected their respective unwanted anomeric impurities at levels lower than 2%. All experiments were performed in 1 minute of total acquisition time demonstrating our method's high-throughput nature. Our methodology was also extended to the separation of an isomeric mixtures of two protected disaccharides illustrating its utility beyond only monosaccharides. We envision our presented workflow as a first step toward the development of a high-throughput screening platform for the rapid and sensitive detection of α/β anomeric selectivities and for trace isomeric/isobaric impurities.